The woman, the lover the reception of selected Filipino women of GMA-7's teleserye, "My Husband's Lover" - Berin, Jannica Faye Moreno 1993-; Austria, Fernando A., Jr.; University of the Philippines Diliman. College of Mass Communication (2014)
"Nowadays, the teleserye has been known as one of the most popular program genres airing in Philippine television. Yet, it is always criticized for having limited and predictable themes such as revenge, love triangles and family conflicts. With that, this study sought to know how selected Filipino women with different meaning structures received GMA-7's teleserye My Husband's Lover, the first ever drama series on mainstream media that portrayed a same-sex relationship in its plot (Togonon, 2013). In order to achieve this goal, I searched for five women who were regular viewers of the said show by utilizing the criterion and snowball sampling techniques. And since I used the Reception Theory, I applied the oral history interview method to gather data on their personal backgrounds and consumption patterns, and on the gender roles prescribed to them now and in the past. The findings of this research showed that the women have received the show through their identification with the submissiveness of its some characters and with the painfulness of love that they have experienced. The said manner of reception of my respondents reflected that they still do adhere to the patriarchal structure that exists in our society today."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines
Keywords: Gay couples on television -- Public opinion -- Philippines; Television soap operas -- Philippines; Women television soap operas -- Attitudes -- Philippines